Penerapan Good Governance dan Sistem Pengendalian Internal Terhadap Kinerja Pengelolaan Keuangan Pada Badan Keuangan Daerah Provinsi Nusa Tenggara Timur - Yohana Talo; Yohanes Demu; Maria P. L. Muga (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to determine the effect of implementing good governance and an internal control system on financial management operations at the Regional Financial Agency of East Nusa Tenggara Province. The total research sample was 36 people. This research uses a type of causal research with a quantitative descriptive research approach. The data analysis technique used in this research is linear multiple regression data analysis. Based on the results of data analysis using linear multiple regression, it shows that the independent variables, namely good governance and the internal control system, have a significant effect on the dependent variable, namely financial management performance, the influence of the independent variable test good governance (X1) and the internal control system (X2) on financial management performance ( Y) of 44.5%.